HUBUNGAN KAUSALITAS DEFISIT NERACA TRANSAKSI BERJALAN DENGAN KURS DI INDONESIA - Purnomo, Didiet; Wahyudi, Wahyudi (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2003)
This research is aimed at understanding the relation pattern of the current transaction balance and Indonesian rate of exchange in 1981-2002. The analysis method used is Granger causality method. Yet, before doing the Granger causality test, it was carried out data stationary test to avoid fake correlation. Stationary test shows that the data are not stationary so that it was made stationary by using one different level. The result of Granger causality analysis shows that it happen only one direction causality relation from the deficit of current account towards the rate of exchange because it has smaller counting F value then the determined a.